ENTREPRENEURIAL SOLUTIONS TO ENVIRONMENTAL CHALLENGES : THE ROLE OF GREEN ENTREPRENEURS IN PROMOTING SUSTAINABLE PRACTICES - Shahverdiyev, Matin (2024)
Abstract: This study investigates how by lowering environmental effects and encouraging creative ideas, green entrepreneurship in the waste management sector of Azerbaijan aids sustainable development. Emphasising five Azerbaijani enterprises, the study looks at how these organisations match their entrepreneurial aims with sustainability goals by including environmentally friendly practices into their operations. By means of theme analysis and methodical interviews, the study reveals important obstacles include insufficient waste separation, public awareness shortcomings, and infrastructure constraints that compromise the success of waste management projects. To solve these problems, though, the businesses are using creative ideas including sophisticated recycling techniques, waste-to-- energy technology, and community education campaigns. Emphasising the necessity of improved infrastructure, public education, and government backing, the results show the vital part of green business in creating a sustainable future in Azerbaijan. According to the report, Azerbaijan's waste management industry may greatly help to meet the sustainable development objectives of the nation by means of ongoing investment in green technology and supporting laws.